Association Between Tuberculosis and Smoking - Alavi-Naini, Roya (Kowsar, 2012)
BACKGROUND: The association between smoking and tuberculosis (TB), which has been proven in multiple studies with different study population ethnicity, has not yet received sufficient attention in terms of TB control. OBJECTIVES: The aim of the present study was to determine the association between TB and cigarette smoking in southeastern Iran, an endemic area for tuberculosis. PATIENTS AND METHODS: This prospective case-control study conducted at a University-Affiliated Hospital (Boo-Ali Hospital, Zahedan, and Southeastern Iran) from March 2007 to March 2012 enrolled 253 TB patients and 312 healthy controls. Factors including history of cigarette smoking, duration of smoking, number of cigarettes smoked per day, consumption of other drugs (parenteral and non-parenteral), and family history of tuberculosis and smoking, were evaluated in both cases and controls. Univarate and multivariate logistic regressions were performed to compare TB cases and controls. The odds ratio (OR) and 95% confidence intervals (CI) were also estimated. RESULTS: The results of the study revealed a significant difference between TB and control groups in relation to smoking (P < 0.0001). In multivariate logistic regression, cigarette smokers were 3.1 (95% CI: 1.4-10.3) times more frequent in TB patients compared with controls. Other factors that showed significant differences between TB patients and controls were the use of non-parenteral drugs (OR = 3.6, 95% CI: 2.2-21.4), family history of TB (OR = 6.6, 95% CI: 2.3-18.2), family history of smoking (OR = 2.8, 95% CI: 1.1-8.4), and smoking history of more than 10 years (OR = 1.6, 95% CI: 1.2-9.8). CONCLUSIONS: The present study evidenced the association between TB and smoking. It is therefore recommended to include interventions for smoking cessation in the current TB control practice.